Monte Alban's Hinterland, Part II : prehispanic settlement patterns in Tlacolula, Etla, and Ocotlan, the Valley of Oaxaca, México - Kowalewski, Stephen A. (Memoirs of the Museum of Anthropology. University of Michigan ;, 1989)
Sumario: Presenta en dos volúmenes un estudio sobre los indios mexicanos en el estado de Oaxaca, México